2015
DOI: 10.5897/ajar2015.10182
|View full text |Cite
|
Sign up to set email alerts
|

Influence of combined sources of nitrogen fertilization on quality of cv. Vitria pineapple

Abstract: Vitória pineapple besides surpassing cultivars traditionally consumed in Brazil, such as Pérola and Smooth Cayenne, exhibits resistance to Fusarium. In this sense, nitrogen fertilization is a critical factor because it interferes with the production and postharvest quality regardless of variety. Thus, this research aimed to evaluate the influence of doses and sources of nitrogen on the content of carbohydrates, bioactive compounds and antioxidant activity of Vitória pineapple cultivar. Five doses of N were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In the 'Smooth Cayenne' pineapple, the ascorbic acid content was reduced in plants with N and K deficiency (Martins et al, 2009), while Dantas et al (2015) reported that nitrogen fertilization above 10 g plant -1 urea and 152 g plant -1 chicken manure, reduced the antioxidant activity of cv. Vitória, probably by the diminution of bioactive compounds like flavonoids and ascorbic acid.…”
Section: /8mentioning
confidence: 99%
“…In the 'Smooth Cayenne' pineapple, the ascorbic acid content was reduced in plants with N and K deficiency (Martins et al, 2009), while Dantas et al (2015) reported that nitrogen fertilization above 10 g plant -1 urea and 152 g plant -1 chicken manure, reduced the antioxidant activity of cv. Vitória, probably by the diminution of bioactive compounds like flavonoids and ascorbic acid.…”
Section: /8mentioning
confidence: 99%
“…Fruit formation results from complex biological processes which begin soon after fertilization (Forlani et al, 2019) and involves a dynamic interplay between phytohormones (McAtee et al, 2013) and availability of essential nutrients (Dantas et al, 2015). These processes include cell division and expansion, accumulation of secondary metabolites, and an increase in carbohydrate biosynthesis (Forlani et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…, considering the diff erence between the color measured in the fi rst period in relation to the other storage periods. Soluble solids were determined in the homogenized pulp, through direct Reading at 20 o C, using a portable digital refractometer (Milwaukee, model -MA871: 0 -85%), with the results expressed as a percentage (DANTAS et al, 2015). The spectrophotometric browning index (OD 420 .g -1 ) of the core was obtained according to Raimbault et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…The pineapple plant is native to Uruguay, Brazil, and Paraguay, and is the most important of the commercially cultivated Bromeliaceae in the tropics and parts of the subtopics (TFnet, 2016) for ornamental purposes (SILVA et al, 2019), but mainly as a fruit of widespread worldwide consumption and trade (SANGPRAYOON et al, 2019). Its infructescence, the pineapple, is highly appreciated for its aroma and fl avor, and is recognized for having nutrients that provide energy to the usual diet and exert powerful biological activities which provide health benefi ts (DANTAS et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation